Impact of riverine suspended particulate matter on the branched glycerol dialkyl glycerol tetraether composition of lakes: The outflow of the Selenga River in Lake Baikal (Russia). - De Jonge, Cindy; Stadnitskaia, Alina; Fedotov, Andrey; Sinninghe Damsté, Jaap S (PANGAEA, 2015)
Branched glycerol dialkyl glycerol tetraethers (brGDGTs) are bacterial membrane lipids found in several environments, including soils, rivers and lakes, whose distribution varies with temperature and pH, although this dependence is apparently not the same for the different environments. Mixing of brGDGT sources may thus complicate palaeoenvironmental reconstruction. The extent to which brGDGTs in a lake outflow reflect the distribution delivered by upstream rivers was studied for Lake Baikal (Russia), one of the largest freshwater lakes worldwide. Fifteen brGDGTs in suspended particulate matter (SPM) of the Selenga River and its outflow from the lake were quantified. The river and lake SPM had rather different distributions. The riverine distribution was still apparent in the SPM of the lake surface water 5 km from the river mouth, but shifts in the distribution were already apparent in the SPM of the surface water after 1 km. Based on the brGDGT distributions of the SPM of the Selenga outflow and that of the lake, conservative mixing between the river and the lake brGDGT distributions could not fully explain the observed shifts in distributions. Both preferential degradation and in situ production of brGDGTs in the surface and, especially, bottom water of the river outflow were potentially responsible. This implies that a riverine lipid distribution delivered to a lake can be modified prior to being transported downstream. The lacustrine brGDGT distribution, that possibly could have reflected a mixture of mountainous and Selenga River SPM, was not recognized in downstream Yenisei River SPM. The watershed of Lake Baikal thus does not seem to contribute to the brGDGTs transported to the marine system. As many large rivers have major lakes in their watershed, this has implications for palaeoclimate reconstruction from river fan sediments globally.
Branched GDGT, crenarchaeol, TOC and bulk δ¹³C in SPM of the Selenga River and its outflow in Lake Baikal, and Lake Baikal outflow in the Yenisei River
Keywords: NIOZ_UU; NIOZ Royal Netherlands Institute for Sea Research, and Utrecht University